2019
DOI: 10.1136/injuryprev-2019-043412
|View full text |Cite
|
Sign up to set email alerts
|

Firearm ownership in California: A latent class analysis

Abstract: ObjectiveTo examine whether firearm ownership and ownership-related motivations and practices can be classified into reasonably distinct types.MethodsCross-sectional data on firearm owners (n=429) were obtained from the 2018 California Safety and Well-Being Survey, a state-representative web-based survey. We conducted a latent class analysis using six self-reported indicators of firearm ownership: (1) number of firearms owned, (2) types of firearms owned, (3) primary reason for firearm ownership, (4) firearm s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…Other research by the authors has demonstrated the existence of distinct typologies of firearm ownership based in part on the number and types of firearms owned, with owners of five or more firearms, including assault-type weapons, more likely to store at least one firearm loaded and unlocked, to own high-capacity magazines, and to have carried a loaded handgun for self-protection in the past 30 days 11. Future research will examine the extent to which these patterns of ownership may be associated with other risk factors for firearm death and injury.…”
Section: Discussionmentioning
confidence: 96%
“…Other research by the authors has demonstrated the existence of distinct typologies of firearm ownership based in part on the number and types of firearms owned, with owners of five or more firearms, including assault-type weapons, more likely to store at least one firearm loaded and unlocked, to own high-capacity magazines, and to have carried a loaded handgun for self-protection in the past 30 days 11. Future research will examine the extent to which these patterns of ownership may be associated with other risk factors for firearm death and injury.…”
Section: Discussionmentioning
confidence: 96%
“…Although the perceived need for selfprotection continues to motivate firearm ownership amid the pandemic, an extensive body of evidence suggests instead that the presence of a firearm in the home elevates risk for firearmrelated harm, particularly unintentional shootings (often involving children), female homicide victimization, and completed suicide. [14][15][16][17] More concerning, perhaps, is that people who own firearms primarily for protection are more likely to store firearms in the home loaded and/or not locked up, 25 an independent risk factor for firearm injury and death. Our findings suggest the pandemic may contribute to this risk: an estimated 55,000 people (1.2% of owners in the state) who currently store at least one firearm loaded and not locked up reported adopting this unsecure storage practice in response to the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…This weight also included corrections to align opt-in respondents with those from KP based on standard sociodemographic characteristics, factors known to differentiate opt-in and probability-based samples, and additional sources of nonsampling errors. Further details on survey methodology are provided elsewhere (Kravitz-Wirtz et al 2019;Schleimer et al 2019).…”
Section: Methodsmentioning
confidence: 99%